Steroid modulation of hippocampal plasticity: switching between cognitive and emotional memories - Maggio, Nicola; Segal, Menahem (Frontiers in Cellular Neuroscience, 2012)
Several new observations have shifted the view of the hippocampus from a structure in charge of cognitive processes to a brain area that participates in the formation of emotional memory. Specifically, while the dorsal hippocampus is involved in the processing of cognitive memories; the ventral sector is mainly associated with the control of behavioral inhibition, stress and emotional memory. Stress is likely to cause this switch in control of hippocampal functions by modulating synaptic plasticity in the dorsal and ventral sectors of the hippocampus through the differential activation of either mineralocorticosteroid (MR) or glucocorticosteroid (GR) receptors. Herein, we will review the effects of stress hormones on synaptic plasticity in the hippocampus and will try to outline the outcomes on stress-related global functions of this structure. We will propose that steroid hormones act as molecular switches: by changing the strength of synaptic connectivity in the hippocampus following stress, and that they regulate the routes by which the hippocampus is functionally linked to the rest of the brain. This hypothesis has profound implications for the pathophysiology of psychiatric disorders.